Achieving high dielectric energy-storage properties through a phase coexistence design and viscous polymer process in BNT-based ceramics - Yule Yang; Juanjuan Wang; Ruiyi Jing; Wenjing Shi; Leiyang Zhang; Chao Li; Xinyu Zeng; Fukang Chen; Gang Liu; Xiaolian Chao; Yan Yan; Li Jin (Journal of Materiomics, 2023)
In the last few decades, dielectric capacitors have gotten a lot of attention because they can store more power and charge and discharge very quickly. But it has a low energy-storage density (Wrec), efficiency (η), and temperature stability. By adding Pb(Mg1/3Nb2/3)O3 (PMN) and (Bi0·1Sr0.85)TiO3 (BST) to a nonstoichiometric (Bi0·51Na0.5)TiO3 (BNT) matrix, the goal is to change the phase transition properties and make the material more relaxor ferroelectric (RFE) by lowering the remnant polarization Pr and keeping the maximum polarization Pmax. A viscous polymer process (VPP) is used to improve the electric breakdown strength, which is also a key part of being able to store energy. By working together, ceramics with the formula 0.79[0.85BNT-0.15PMN]-0.21BST (BP-0.21BST) are made. The phase structure has been changed from a rhombohedral phase to a rhombohedral-tetragonal coexisted phase. This is beneficial for RFE properties and gives a Wrec of 6.45 J/cm3 and a η of 90% at 400 kV/cm. Also, the energy-storage property is very temperature stable between 30 and 150 °C. These results show that process optimization and composition design can be used to improve the energy storage properties, and that the dielectric ceramic materials made can be used in high-powder pulse dielectric capacitors.